Investor type heterogeneity in bottom-up optimization models - Mathias Mier; Valeriya Azarova (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Bottom-up optimization models neglect the inclusion of investment behavior We introduce three investor types that differ in their investment cost specifications, financing costs, and discounting. This leads to a substantially different pace and rate of adoption for specific generation technologies. For the European power market, 2050 wind (nuclear, gas-CCS) capacity ranges from 624 to 1,113 GW (84 to 194 GW, 383 to 502 GW), depending on the respective investor type. Accounting for type heterogeneity leads to 2050 wind (nuclear, gas-CCS) capacity of 912 GW (140 GW, 428 GW). Technologyspecific financing cost increase 2050 wind (nuclear, gas-CCS) capacity even to 1,069 GW (80 GW, 449 GW). Hence, our results confirm that accounting for more differentiated picture of electricity market investment with heterogeneous investor types can provide a starting point for tailor-made energy policies, thereby increasing the efficiency and effectiveness of public policies fostering the decarbonization of power markets.
Keywords: C61; C68; Q40; Q41; 330; Investment behavior; investor type; investment cost; bottom-up optimization model; energy system model; power market model